Comparative Immunopathology of Cetacean morbillivirus Infection in Free-Ranging Dolphins From Western Mediterranean, Northeast-Central, and Southwestern Atlantic - Díaz-Delgado, Josué; Groch, Kátia R.; Ressio, Rodrigo; Riskallah, Isis P. J.; Sierra, Eva; Sacchini, Simona; Quesada-Canales, Óscar; Arbelo, Manuel; Fernández, Antonio; Santos-Neto, Elitieri; Ikeda, Joana; Carvalho, Rafael Ramos de; et al. (Frontiers in Immunology, 2019)
Cetacean morbillivirus (CeMV; Paramyxoviridae) causes epizootic and interepizootic fatalities in odontocetes and mysticetes worldwide. Studies suggest there is different species-specific susceptibility to CeMV infection, with striped dolphins (Stenella coeruleoalba), bottlenose dolphins (Tursiops truncatus) and Guiana dolphins (Sotalia guianensis) ranking among the most susceptible cetacean hosts. The pathogenesis of CeMV infection is not fully resolved. Since no previous studies have evaluated the organ-specific immunopathogenetic features of CeMV infection in tissues from infected dolphins, this study was aimed at characterizing and comparing immunophenotypic profiles of local immune responses in lymphoid organs (lymph nodes, spleen), lung and CNS in CeMV-molecularly (RT-PCR)-positive cetaceans from Western Mediterranean, Northeast-Central and Southwestern Atlantic. Immunohistochemical (IHC) analyses targeted molecules of immunologic interest: caspase 3, CD3, CD20, CD57, CD68, FoxP3, MHCII, Iba1, IFNγ, IgG, IL4, IL10, lysozyme, TGFβ and PAX5. We detected consistent CeMV-associated inflammatory response patterns. Within CNS, inflammation was dominated by CD3+ (T cells), and CD20+ and PAX5+ (B cells) lymphocytes, accompanied by fewer Iba1+, CD68+ and lysozyme+ histiocytes, mainly in striped dolphins and bottlenose dolphins. Multicentric lymphoid depletion was characterized by reduced numbers of T cells and B cells, more pronounced in Guiana dolphins. Striped dolphins and bottlenose dolphins often had hyperplastic (regenerative) phenomena involving the aforementioned cell populations, particularly chronically infected animals. In the lung, there was mild to moderate increase in T cells, B cells and histiocytes. Additionally, there was a generalized increased expression of caspase 3 in lymphoid, lung and CNS tissues. Apoptosis, therefore, is believed to play a major role in generalized lymphoid depletion and likely overt immunosuppression during CeMV infection. No differences were detected regarding cytokine immunoreactivity in lymph nodes, spleen and lung from infected and non-infected dolphins by semiquantitative analysis; however, there was striking immunoreactivity for IFNγ in the CNS of infected dolphins. These novel results set the basis for tissue-specific immunophenotypic responses during CeMV infection in three highly susceptible delphinid species. They also suggest a complex interplay between viral and host’s immune factors, thereby contributing to gain valuable insights into similarities and differences of CeMV infection’s immunopathogenesis in relation to body tissues, CeMV strains and cetacean hosts.